Analisis Kemampuan Guru Mata Pelajaran Ekonomi Dalam Pengelolaan Kelas X Sman 8 Malang - Puji Irawati; Sri Umi Mintarti (Universitas Negeri Malang, 2016)
The ability of teachers to manage a class which the teacher is very important to create and maintain a learning conditions and activities become optimal in case of disturbances during the learning process. This study is to determine the ability of classroom management examined included the ability to provide responsiveness, dividing attention, focusing groups, provide clear guidance, reprimand, provide reinforcement, behavior modification, manage groups, find and solve behavior that cause problems, and avoid some of the mistakes in the classroom. This research method was using descriptive qualitative approach, type of research used in this research was phenomenology. The subjects in this study is one of the economic teacher in grade X SMAN 8 Malang which certified and the students of grade X. The research instruments used were observation and interviews. Methods of data collection using observation, interview and documentation techniques. Analysis of data using Data Reduction, Presentation of Data, and collecting Conclusions and Verification. Research results show that the ability of teachers in the management of economic subjects in grade X SMAN 8 Malang have been effective. Meanwhile in response attitude indicator, dividing attention, focusing groups, give clear instructions, admonishing student, provide reinforcement, behavior modification, manage groups, find and solve behavior that cause problems, and avoid some of the mistakes in the classroom have been effective. Keywords: The ability of classroom management, classroom management on grade X SMAN 8 Malang